Fatty acid, fat-soluble vitamin and sterol contents in testis and semen, testis-somatic index and spermatologic values of broodstock rainbow trout (Oncorhynchus mykiss) fed with different levels of omega-3 fatty acids under regular stripping conditions - Koprucu, Kenan; Ozcan, Sinan (Wiley, 2019)
In this study, the testis and semen fatty acid, fat-soluble vitamin and sterol levels, testis-somatic index and spermatological values were investigated in the broodstock rainbow trout fed with the different levels of omega-3 polyunsaturated fatty acid (PUFA) under the regular stripping conditions. For this purpose, a control and three test diets were prepared. The control, D1, D2 and D3 diets were contained the omega-3 PUFA at 3.14%, 7.84%, 13.63% and 20.54% as a percentage of the total fatty acids respectively. The fish in the experimental groups were fed with these diets for 60 days. The testis-somatic index (3.81-4.50), semen volume (9.30-18.5 ml) and pH (8.05-8.99), initial sperm motility (68.1%-93.7%), duration of 50% sperm motility (141.3-258.9 s), total duration of sperm motility (268.7-489.6 s) and sperm density (9.95-17.5 cells x 10(9) ml(-1)) values of the fish fed the control diet were significantly decrease (p < 0.05) depending on decline of the omega-3 PUFA, fat-soluble vitamin and sterol contents in the testis and semen. The omega-3 PUFA (3.40%-14.76% and 3.96%-16.31%), vitamin A (33.9-61.2 ml/mg and 9.12-26.7 ml/mg), D-2 (0.10-0.19 ml/mg and 0.04-0.10 ml/mg), D-3 (0.75-1.30 ml/mg and 0.06-0.24 ml/mg), alpha-tocopherol (30.1-60.4 ml/mg and 8.93-25.3 ml/mg), K-1 (0.30-0.94 ml/mg and 0.03-0.08 ml/mg) and K-2 (2.0-3.19 ml/mg and 0.25-0.34 ml/mg) vitamins, cholesterol (1,201-1,588 ml/mg and 330-596 ml/mg), ergosterol (3.12-6.40 ml/mg and 2.10-4.08 ml/mg), stigmasterol (5.57-10.4 ml/mg and 10.2-12.6 ml/mg) and beta-sitosterol (0.20-0.60 ml/mg and 0.14-0.41 ml/mg) contents in the testis and semen of the fish were significantly affected (p < 0.05) by the dietary omega-3 PUFA supplementation. The highest values for these parameters were provided from the fish fed the D2 and D3 diets (p > 0.05), followed by the fish fed the D1 diet (p < 0.05). These results showed that the dietary omega-3 PUFA at 13.63% of the total fatty acids could increase the omega-3 PUFA, fat-soluble vitamin and sterol contents in the testis and semen, the testis-somatic index and spermatologic values of the broodstock rainbow trout under the regular stripping conditions.
Keywords: fat-soluble vitamins; fatty acids; rainbow trout; sperm; sterols; testis